Analytical and clinical validation of a high accuracy fully automated digital immunoassay for plasma phospho-Tau 217 for clinical use in detecting amyloid pathology - Wilson, David; Khare, Meenakshi; Triana-Baltzer, Gallen; Wolfe, Michele; Sheehy, Patrick; Copeland, Karen; Hesterberg, Lyndal; Vasko, Ann-Jeanette; van der Flier, Wiesje M.; Verberk, Inge M. W.; Teunissen, Charlotte E.; Miller, Mike (Frontiers in Neurology, 2025)
BackgroundWith the emergence of disease-modifying therapies for Alzheimer’s disease (AD), there is an urgent need for scalable, accurate, and well-validated blood test alternatives to positron emission topography (PET) and lumbar punctures for identifying amyloid pathology to facilitate identification of candidates for therapy. Plasma p-Tau 217 has emerged as a plasma-based biomarker with sufficient sensitivity and specificity to both rule out and rule in amyloid pathology with high confidence, potentially serving as a readily scalable non-invasive test to aid AD diagnosis. In this report, we describe robust analytical and clinical validation of a lab developed test for plasma p-Tau 217 suitable for clinical diagnostic use.MethodsA high sensitivity digital immunoassay using single molecule array (Simoa) technology was developed for plasma p-Tau 217 utilizing a 2-cutoff approach. The assay was analytically validated with industry standard protocols and clinically validated across 873 symptomatic individuals from two independent clinical cohorts using PET or cerebrospinal fluid (CSF) biomarkers as comparators.ResultsThe assay exhibited acceptable analytical characteristics with an analytical sensitivity enabling measurement of plasma p-Tau 217 in all clinical samples. Excluding results between the two cutoffs, clinical sensitivity, specificity, and agreement with comparator methods (accuracy) were >90%, with 30.9% of the samples falling in the intermediate zone between the two cutoffs.DiscussionThe performance characteristics of the Simoa p-Tau 217 assay align with current accuracy recommendations for blood-based biomarker test performance for diagnostic use, making the test suitable for clinical use under the Clinical Laboratory Improvement Act (CLIA) as a diagnostic plasma test to aid in Alzheimer’s diagnosis.